CHARACTER EDUCATION AS AN EFFORT TO REDUCE THE RATE OF MENTAL DISEASE IN THE MILLENNIAL GENERATION - Ambarwati, Galuh Adjeng; Pandin, Moses Glorino Rumambo (Ganesha Civic Education Journal, 2024)
Character education is an activity of people who teach good works to educate the next generation, especially the millennial generation, to think and behave, to form mental health in humans permanently, and to educate creativity and inner knowledge to become guidelines and pillars for the future. This article aims to provide knowledge of character education from an early age to a productive period, especially for the millennial generation, in order to reduce mental illness. The method of writing this article uses a literature review, namely a summary of 10 articles in the years of publication starting from 2019, 2020, and 2021 on search web pages, articles, and Google Scholar according to keywords. The eligibility of this research institution is seen from the title, abstract, research methodology, results, and discussion. The results of the study are presented in narrative form, and the results of the 10 study articles show several causes of mental health so far. Therefore, character education is needed from an early age. The implication is that the number of mental illnesses can be eliminated by providing character education from an early age so that knowledge about actions and behaviors can shape the mentality of the generation to be stronger. Thus, character education is a solution to reduce the number of mental illnesses in the millennial generation.